Dysphagia management in Parkinson's disease: Comparison of the effect of thickening agents on taste, aroma, and texture. Issue 3 (31st January 2021) - Baert, Florence; Vlaemynck, Geertrui; Beeckman, Anne‐Sophie; Van Weyenberg, Stephanie; Matthys, Christophe
Abstract: Dysphagia is a frequent symptom in Parkinson's disease (PD). Thickening liquids facilitates safe swallowing, however, low treatment compliance is a major issue, due to patients' dislike of thickened liquids. Some studies suggest a negative impact of gum‐based thickeners, currently most used in clinical practice, on sensory properties compared to starch‐based thickeners. This has not yet been investigated in PD. This study's aim was to compare taste, texture, and aroma of gum‐based and starch‐based thickened soups in participants with PD. Gum‐based resource thicken up clear (RTUC) and starch‐based kitchen products potato starch (PS) and quinoa flour (QF) were evaluated in broccoli soup. Texture, aroma, and taste were characterized by rheology, volatile, and sensory profiling. Thickened soups were evaluated in participants with PD and controls through a paired comparison test. Reduced release of 61.4%, 46.2%, and 38.5% of volatiles was observed after thickening with RTUC, PS, and QF, respectively. Overall taste intensity was reduced in RTUC‐ and PS‐thickened soup, respectively. Taste and aroma of PS‐thickened soup were considered more intense by 70.3% and 63.8% of all participants, respectively ( n = 36 PD, n = 41 controls), 56.3% preferred the PS‐thickened soup's texture . Taste and aroma of QF‐thickened soup were considered more intense by 68.1% and 65.6% of all participants, respectively ( n = 47 PD, n = 31 controls), 58.0% preferred the QF‐thickened soup's texture. Starch‐based thickeners demonstrated higher taste and aroma intensity. However, volatile and sensory profiling demonstrated reduced taste and aroma in all thickeners. Combining kitchen products with flavor enhancers may increase palatability of thickened beverages.